2019
DOI: 10.3389/fbuil.2019.00101
|View full text |Cite
|
Sign up to set email alerts
|

Forming Mechanism of Political Risks in International Construction Projects: From the Perspective of Chinese Contractors

Abstract: The performance is analyzed from the perspective of the characteristics of overseas business of Chinese contractors and political risks. Based on the results of this research project, the funds and pricing model of Chinese Contractors Overseas Projects were further analyzed, as well as their ability to withstand political risks and coping strategies. The purpose of this study was to study the statistical analysis of risks in design systems and international activities within the framework of international cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Researchers have identified a number of risks threatening the safety of overseas Chinese workers in the construction industry. For example, Ullah et al [ 57 ] found the political risks such as conflicts and wars can not only affect the success of projects but also pose a great threat to the personal safety of Chinese employees in Africa. Du [ 58 ] maintained that besides political instability, economic risks, and corruption in the host country, security risks also arise from the misbehavior of employees themselves.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have identified a number of risks threatening the safety of overseas Chinese workers in the construction industry. For example, Ullah et al [ 57 ] found the political risks such as conflicts and wars can not only affect the success of projects but also pose a great threat to the personal safety of Chinese employees in Africa. Du [ 58 ] maintained that besides political instability, economic risks, and corruption in the host country, security risks also arise from the misbehavior of employees themselves.…”
Section: Literature Reviewmentioning
confidence: 99%